On the long-range dependence of packet round-trip delays in Internet - Qiong Li; Mills, D.L. (1998 IEEE International Conference on Communications, 1998)
Many previous studies on network traffic demonstrate that long-range dependence (LRD) is a ubiquitous property of traffic both in a local area network (LAN) and a wide area network (WAN). So the performance of the network should be dominated by this property. The packet round-trip delay is an important measurement of network performance. We present evidence that LRD exists in packet round-trip delays. This discovery has serious implications for understanding the impact on network performance of LRD network traffic, and the design of transport control protocols for special applications, i.e., of teleconferencing. Statistical analyses show that the complementary probability distribution of packet round-trip delays decays more slowly than at an exponential rate; this fact probably justifies the studies on the prediction of the queue length distribution with LRD network traffic. We also tentatively use a multi-queueing system to interpret the existence of LRD in the packet round-trip delay process, which we believe is caused by the LRD of Internet traffic.